Penanaman Nilai-nilai Moderasi Beragama Siswa melalui Pembelajaran Aqidah Akhlaq di MA Bahauddin Ngelom Sidoarjo - Ali, Muhammad As'ad; Rodiyah, Siti Kholidatur; Al Chumairoh, Nailul Ulah (YASIN, 2025)
The issue of religious moderation is important. School education plays a vital role in the process of instilling these values ​​of moderation. The urgency is reinforced by the influence of the modern era and the challenges of increasingly rampant urban society. In a case study, a phenomenon of educational institutions in urban areas was found that still maintain the content of ethical and moral education and insert moderation content. Of the many institutions that are competing to strengthen these values, MA Bahauddin Ngelom Sidoarjo is one of them. In addition to reasons from the urban space side that make it very possible for multicultural problems to occur, MA Bahauddin is also a private institution that is of interest to many applicants. The purpose of this study is to narrate how to instill the values ​​of religious tolerance through Aqidah Akhlak lessons at MA Bahauddin along with supporting and inhibiting factors. This study is a qualitative study and the data collection method is through interviews, personal documents, memos, and other official documents. This study has produced several conclusions, including; First, the instillation of religious tolerance values ​​in students' aqidah akhlaq learning at MA Bahauddin Ngelom Sidoarjo is going well and effectively, as evidenced by the systematic stages in learning aqidah akhlaq including the introduction of tolerance values, instillation through learning and experience, internalization of tolerance values, reinforcement and appreciation. Second, supporting factors in the process of instilling tolerance values ​​through learning Aqidah Akhlak at MA Bahauddin include the existence of government policies related to religious tolerance in educational institutions, the existence of adequate learning facilities and resources, support from the head of the madrasah and madrasah stakeholders, literature on aqidah akhlaq materials that emphasize the value of religious tolerance, inclusive madrasah management, and a tolerant surrounding community environment. While some inhibiting factors are the level of differences in students' abilities and emotional maturity, differences in the origins of previous schools, limited time in learning aqidah akhlak, some students pay less attention and are sleepy during learning.